2014
DOI: 10.4236/ojcd.2014.44032
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Use of Growth Factors in the Improvement of Skin Wound Healing

Abstract: To discuss the normal mechanism of wound healing (WH), the role of growth factors (GF) in preclinical and clinical studies and its importance in the healing of abnormal wound therapy. For search, we used the PUBMED and LILACS database, and the following descriptors: skin, wound healing, growth factor and clinical trials. We also prioritized the analysis of the Clinical Trials in the previous 10 years. Although there are many studies being conducted in the pre-clinical phase, we see that there are few studies i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…This growth factor is produced by inflammatory cells, endothelial cells, fibroblasts, and keratinocytes. The mechanism of FGF-2 in the wound healing process has been known both in vitro and in vivo, namely through its mechanism in activating local macrophages, increasing the production of extracellular matrix components, fibroblast proliferation, proliferation and migration of endothelial cells for angiogenesis and re-epithelialization (Cornick et al 2014). The study by Tanaka et al (1996) showed a decreased amount of FGF-2 in a diabetic rat model.…”
Section: Discussionmentioning
confidence: 99%
“…This growth factor is produced by inflammatory cells, endothelial cells, fibroblasts, and keratinocytes. The mechanism of FGF-2 in the wound healing process has been known both in vitro and in vivo, namely through its mechanism in activating local macrophages, increasing the production of extracellular matrix components, fibroblast proliferation, proliferation and migration of endothelial cells for angiogenesis and re-epithelialization (Cornick et al 2014). The study by Tanaka et al (1996) showed a decreased amount of FGF-2 in a diabetic rat model.…”
Section: Discussionmentioning
confidence: 99%